Gravitational F-terms through Konishi anomaly - Alday, L (2004)
We review in a pedagogical way the computation of gravitational corrections to the effective superpotential of N = 1 supersymmetric gauge theories coupled to supergravity, by using the method of the generalized Konishi anomaly. We focus on the first non-trivial gravitational corrections to U (N) gauge theories with a single adjoint chiral multiplet, and briefly comment on some generalizations.